Can the integration of agriculture and tourism foster agricultural green development? An empirical analysis based on panel data from 30 provinces in China - Chen, Chen; Wang, Jingjing; Jiang, Weiguo; Xie, Ailiang (Frontiers in Sustainable Food Systems, 2025)
The integration of agriculture and tourism, grounded in agricultural resources, not only offers new development opportunities for the agricultural sector but also steers it towards a greener and more sustainable trajectory. Using panel data from 30 provinces in China from 2011 to 2022, this study quantifies the levels of agriculture and tourism integration (ATL) and agricultural green development (AGD) in each province. Then, the study applies the fixed effects model, the spatial Durbin model, and the panel smooth transition regression (PSTR) model to empirically assess the impact of ATL on AGD, as well as its spatial spillover effect and its nonlinear characteristics. The findings are as follows: (1) Over the study period, both AGD and ATL exhibited steady growth, with marked spatial agglomeration effects; (2) ATL positively influenced AGD, suggesting that the integration of agriculture and tourism contributes to the green development of agriculture; (3) The impact of ATL on AGD exhibited significant spatial spillover effects, meaning that integrated agricultural-tourism development in one region can enhance AGD in its neighboring provinces; (4) The effect of ATL on AGD demonstrated nonlinear characteristics, with the influence of ATL on AGD intensifying as ATL increased. Based on these findings, the study proposes several policy recommendations, including strengthening top-level policy design, improving regional coordination mechanisms, and enhancing human capital cultivation, to foster deeper the integration of agriculture and tourism and to further accelerate the green development of agriculture.